Colonial empires compared : Britain and the Netherlands, 1750-1850 : papers delivered to the fourteenth Anglo-Dutch Historical Conference, 2000 /: Britain and the Netherlands, 1750-1850 : papers delivered to the fourteenth Anglo-Dutch Historical Conference, 2000. (2017) - Unknown
No abstract available